Cinematic Features in the Camel Trip of Abu Tammam - Al-Anqari, Nuwayyir Fahad (Al-Ḍād Journal, 2025)
The current research aimed to approach a field of research that, to my mind, has not been widely explored in classical poetry, despite its significant subject matter. It aimed to discuss the classical poetry in general and the poetry of Abu Tammam in particular, from a critical perspective according to modern approaches, thus revealing the aesthetics of brilliance and astonishment that distinguished the classical poet. It also aimed to explore the cinematic techniques Abu Tammam used to transform the traditional camel’s journey in Arabic poetry into a visual medium. It includes an introduction with two topics: the presence of the camel’s journey in classical poetry, as well as an overview of the relationship between poetry and cinema. The first is entitled: "The Camera Shot" and the second "Cinematic Montage". A conclusion summarizes the most prominent findings of the research, which are: Classical poetry is a rich resource of cinematic manifestations, and Abu Tammam is one of the most prominent poets whose poetry incorporates these manifestations without the poet’s intention. In the camel’s journey, Abu Tammam focused on describing the details of all its body parts, particularly color and size. Abu Tammam depended on a sequence of shots and scenes, intercutting between them in a narrative style resembling the montage in a film to enhance the visual image. Thus, the poet was able to employ cinematic techniques in a striking manner that merits research and study. Keywords: The Camel’s Journey, Abu Tammam, Camera Shot, Montage.